Features of the chromosome set of representatives of smoothnosed bats of the North Caucasus - R. I. Dzuyev; M. A. Khashkulova; V. N. Kanukova; E. A. Baragunova; R. K. Sabanova; А. A. Cheprakova; B. A. Dzagurov; A. R. Dzuyev (Юг России: экология, развитие)
Aim. The aim of this work was to study the chromosome set of some representatives of smooth-nosed bats of the North Caucasus.Material and Methods. Various research methods were used to achieve this goal, including that of dried preparations (the main method for obtaining chromosomal preparations) and that of constructing karyograms.Results. A comparative analysis of the karyological data of 11 species of smooth-nosed bats of the North Caucasus was undertaken and the karyological characteristics of the species accepted in the latest reports on the fauna of Russia and the Caucasus were clarified. The similarity of G -bands in large pairs of meta- and submetacentric chromosomes in Myotis blythi, Myotis mystacinus, Pipistrellus pipistrellus, Pipistrellus kuhli and Vepertilio murinus with bands in small and medium-sized acrocentric chromosomes such as in Eptesicus seotinus may indicate the evolution of the karyotype of the first species by Robertsonian translocation, i.e. compounds of acrocentric chromosomes of Eptesicus serotinus in various combinations. When comparing karyotypes in the family Vespertilionidae, it was found that the karyotype of Eptesicus serotinus is "archaic" (2n=50, NFa=48). With the help of karyological data, the authors composed schemes of phylogenetic relationships of genera in the family Vespertilionidae, which differ to a certain extent from the schemes compiled by taxonomists for representatives of this family.Conclusions. Based on the results obtained, we can conclude that the karyotype of Eptesicus serotinus is the most primitive among the representatives of the order of bats. The primary role in the evolution of this group was played by Robertsonian rearrangements and pericentric inversions (reduction of NFa and 2n from 50 to 38).